DESIGNING MOBILE-BASED APPLICATION FOR QUANTIFYING IT BUSINESS VALUE - Stanley Karouw (Faculty of Computer Science Universitas Indonesia, 2014)
Abstract North Sulawesi province is fostering regional development towards a society which have values, prosperous and competitive cultures. Information Technology (IT) have become a key enabler to accelerate region developments. To optimize IT utilization, local government can used IT Valuation Matrix framework, to identify all IT Business Value which derived from each IT investing type, and then be quantify in reasonable and responsible manner. IT Valuation Matrix framework also provide best practices to assessing local government IT investment. This article shows the process of designing mobile-android based applications for quantifying IT Business Value based on IT Valuation Matrix method. Using Disciplined Agile Delivery methodology, which based on agility and object-oriented approach, the application that meet user expectations and needs, can be developed.